Macrophage migration inhibitory factor contributes to ethanol‐induced liver injury by mediating cell injury, steatohepatitis, and steatosis1. Issue 5 (18th January 2013) - Barnes, Mark A.; McMullen, Megan R.; Roychowdhury, Sanjoy; Pisano, Sorana G.; Liu, Xiuli; Stavitsky, Abram B.; Bucala, Richard; Nagy, Laura E.
Abstract: Macrophage migration inhibitory factor (MIF), a multipotent protein that exhibits both cytokine and chemotactic properties, is expressed by many cell types, including hepatocytes and nonparenchymal cells. We hypothesized that MIF is a key contributor to liver injury after ethanol exposure. Female C57BL/6 or MIF−/− mice were fed an ethanol‐containing liquid diet or pair‐fed control diet for 4 (11% total kcal;early response) or 25 (32% kcal; chronic response) days. Expression of MIF messenger RNA (mRNA) was induced at both 4 days and 25 days of ethanol feeding. After chronic ethanol, hepatic triglycerides and plasma alanine aminotransferase (ALT) and aspartate aminotransferase (AST) were increased in wildtype, but not MIF−/−, mice. In order to understand the role of MIF in chronic ethanol‐induced liver injury, we investigated the early response of wildtype and MIF−/− to ethanol. Ethanol feeding for 4 days increased apoptosis of hepatic macrophages and activated complement in both wildtype and MIF−/− mice. However, tumor necrosis factor alpha (TNF‐α) expression was increased only in wildtype mice. This attenuation of TNF‐α expression was associated with fewer F4/80+ macrophages in liver of MIF−/− mice. After 25 days of ethanol feeding, chemokine expression was increased in wildtype mice, but not MIF−/− mice. Again, this protection was associated with decreased F4/80+ cells in MIF−/− mice after ethanol feeding. Chronic ethanol feeding also sensitized wildtype, but not MIF−/−, mice to lipopolysaccharide, increasing chemokine expression and monocyte recruitment into the liver. Conclusion : Taken together, these data indicate that MIF is an important mediator in the regulation of chemokine production and immune cell infiltration in the liver during ethanol feeding and promotes ethanol‐induced steatosis and hepatocyte damage. (HEPATOLOGY 2013)